Latin American Trade Policies in the 1970's: A Comment - Balassa, Bela (Quarterly Journal of Economics, 1975)
Journal Article Latin American Trade Policies in the 1970's: A Comment Get access Bela Balassa Bela Balassa International Bank for Reconstruction and Development Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 89, Issue 3, August 1975, Pages 483–486, https://doi.org/10.2307/1885268 Published: 01 August 1975